GREEN ECONOMY DENGAN PENGELOLAAN LIMBAH BERBASIS ILMU PENGETAHUAN DAN TEKNOLOGI PADA BANK SAMPAH 3G - Masripah, Siti; Purwandani, Indah; Nurhayaty, Ety (Jurnal AbdiMas Nusa Mandiri, 2024)
Garbage remains a significant issue in Greenary Permai Bojong Gede Housing, leading to an unhealthy environment, particularly when waste collection is inconsistent. In response, the 3G waste bank initiated several waste reduction activities. However, progress has been slow due to limited waste management knowledge, incomplete equipment, low community awareness, and manual record-keeping. To address these challenges, training was provided on managing organic and plastic waste, and repurposing used cooking oil into candles and soap. Financial application training was also given to improve the recording process. The goal was to enable the community and partners to adopt a small-scale waste management system and integrate it into daily habits. Using Participatory Action Research (PAR), community members, including waste bank administrators, were directly involved in hands-on training to ensure participants understood the objectives. Since the socialization of this initiative in April 2024, significant progress has been made. Questionnaire results showed 95% of participants understood the activity's purpose. Monitoring and evaluation revealed that residents and partners have successfully adopted composting, ecobrick-making, and proper recycling of used cooking oil into candles or soap, demonstrating sustainable practices and optimal use of the financial applications.